Homozygosity mapping identified a novel protein truncating mutation (p.Ser100Leufs*24) of the BBS9 gene in a consanguineous Pakistani family with Bardet Biedl syndrome. Issue 1 (December 2016) - Khan, Muzammil; Mohan, Sumitra; Zubair, Muhammad; Windpassinger, Christian
Abstract Background Bardet Biedl Syndrome (BBS) is a rare condition of multi-organ dysfunction with characteristic clinical features of retinal degeneration, truncal obesity, postaxial polydactyly, genital anomaly, intellectual disability and renal dysfunction. It is a hetero-genetic disorder and nineteen BBS genes have been discovered so far. Methods Whole genome SNP genotyping was performed by using CytoScan® 750 K array (Affymetrix). Subsequently, the segregation of the disease locus in the whole family was carried out by genotyping STS markers within the homozygous interval. Finally, the mutation analysis was performed by Sanger DNA sequencing. Results In the present molecular study a consanguineous Pakistani family, with autosomal recessive BBS, was analyzed. The clinical analysis of affected individuals presented with synpolydactyly, obesity, intellectual disability, renal abnormality and retinitis pigmentosa. The presented phenotype was consistent with the major features of BBS syndrome. Homozygosity mapping identified a common homozygous interval within the known BBS9 locus. Sequence analysis ofBBS9/PTHB1 gene revealed a single base deletion of c.299delC (p.Ser100Leufs*24) in exon 4. This frame-shift mutation presumably leads to a 122 amino acid truncated protein with complete loss of its C-terminal PTHB1 domain in combination with a partial loss of the N-terminal PTHB1 domain as well.BBS9/PTHB1 gene mutations have been shown to be associated with BBS syndrome and to the best of our knowledge this study reports the first Pakistani family linked to theBBS9 gene. Conclusion Our molecular findings expand the mutational spectrum ofBBS9 gene and also explain the genetic heterogeneity of Pakistan families with BBS syndrome. The growing number of mutations in BBS genes in combination with a detailed phenotypical description of patients will be helpful for genotype-phenotype correlation, targeted genetic diagnosis, prenatal screening and carrier testing of familial and non-familial BBS patients.